Enhancing Irrigation Efficiency Through the Selection of Sprinkler Machine Design - R. N. Zadorozhniy; I. V. Romanov (Сельскохозяйственные машины и технологии)
The expansion of agricultural production implies an accelerated pace of development of water supply systems in agricultural areas. Water is consumed during animal breeding, primary processing of raw materials, preparation of liquid fertilizers, for household and other needs. Large volumes of water are spent on preparing liquid fertilizers when growing crops and irrigating fields. To increase moisture reserves in the root layer of the soil and increase land fertility, it is necessary to carry out irrigation measures. Sprinkling is one of the most common methods of irrigation. Taking into account the characteristics of the terrain, the type of agricultural products grown, as well as the security of a particular farm, you should choose certain sprinkler machines that will ensure high irrigation efficiency. Sprinklers can be classified according to their principle of operation, type and type, as well as according to the transformation of water flow. (Research purpose) Improving irrigation efficiency by selecting the optimal parameters of sprinklers based on local conditions. (Materials and methods) The object of the study was sprinkling machines, their performance and technical characteristics, as well as the features of the relief. The following research methods were used: analysis of literary sources; logical analysis of existing experimental data on irrigation processes; evaluation of the effectiveness of the use of specific machines and equipment; statistical data processing. (Results and discussion) The paper describes the design and operation of various sprinklers, provides irrigation schemes and calculations of its intensity. Shortcomings of specific irrigation schemes and types of sprinklers were identified, and ways to eliminate them were proposed. (Conclusions) The choice of irrigation scheme depends on the area of the site and its topography. Depending on the budget of the farm, you can choose the most optimal type of sprinkler.